Perspektif Khaled Abou el-Fadl dalam Membendung Otoritarianisme Tafsir Keagamaan melalui Hermeneutika Negosiatif - Qudsi, Saifudin (Religió: Jurnal Studi Agama-agama, 2013)
Leading authoritarianism on religious interpretation which is almost practiced by religious organizations or religious groups, in the name of God, is one of Khaled Abou El-Fadl’s academic questions. By using hermeneutical method, Khaled attempts to reconstruct contemporary despotism and authoritarianism in the field of religious interpretation. The main focus of Khaled’s idea is that authority in Islamic law is different from authoritarianism. It is to avoid tyranny within authoritative interpretation. Khaled offers a negotiative hermeneutics which notices that meaning is an interactive result between the author, text and reader. The negotiative hermeneutics a la Khaled tries to connect the limitless opening of the text and the arbitrary closing of the text. This method suggests the dialog between traditions, communities of interpreters, scientific disciplines, and civilizations. The result of this concept is that to counter religious authoritarianism, exclusivism, puritanism, and anarchy. This article aims for looking Khaled Abou El-Fadl’s way of thinking in relation with religious interpretation which is almost used by religious organization or group. The main frame of this paper is to look on how hermeneutical method proposed by Khaled gives a new innovation in seeing the development of Islamic studies